FGF Signaling in Lung Development and Disease: Human Versus Mouse - Danopoulos, Soula; Shiosaki, Jessica; Al Alam, Denise (Frontiers in Genetics, 2019)
Fibroblast growth factor 10 (FGF10) plays an important role in mouse lung development, injury and repair. It is considered the main morphogen driving lung branching morphogenesis in rodents. While many studies have found FGF10 SNPs associated with COPD and branch variants in COPD smokers, there is no evidence of a causative role for FGF10 or these SNPs in human lung development and pediatric lung diseases. We and others have shown divergent roles for FGF10 in mouse lung development and early human lung development. Herein, we only review the existing literature on FGF signaling in human lung development and pediatric human lung diseases, comparing what is known in mouse lung to that in human lung.